Development and reform of neurosurgical critical care management. - FENG, Guang (Chinese Journal of Contemporary Neurology & Neurosurgery, 2025)
Over decades of development, the management of diagnosis and treatment in neurocritical care medicine has evolved from single-parameter monitoring to multimodal neuromonitoring. Through the integration of intracranial pressure (ICP), cerebral blood flow, brain function and other multi-parameter monitoring data, combined with artificial intelligence (AI) and big data model, it can realize the risk early warning of multiple complications. Digital and intelligent technologies are driving innovations in diagnosis and treatment. Although facing challenges such as difficult data standardization and model adaptation, it will continue to develop towards precision, individualization, digital intelligence and networking in the future.